Approximation and Shape-Preserving Properties of $Q$-Stancu Operator (Analysis in Theory and Applications, 2011)
We introduce the definition of $q$-Stancu operator and investigate its approximation and shape-preserving property. With the help of the sign changes of $f (x)$ and $L_n = f ( f ,q;x)$ the shape-preserving property of $q$-Stancu operator is obtained.
Keywords: $q$-Stancu operator; shape-preserving property; sign change.